2022
DOI: 10.1177/00099228221140801
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Recalcitrant Pediatric Pemphigus Vulgaris With Rituximab

Abstract: Figure 1. Note multiple erosions and scattered flaccid bullae involving almost 100% of patient's back.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…At present, the earliest research on rituximab in the treatment of pemphigus can be traced back to the successful treatment case published by Heizmann, M in 2001 [ 91 ], who proposed that rituximab may be an effective alternative drug for the treatment of PNP. Rituximab can be used alone to treat pemphigus [ 92 , 93 ] or in combination with glucocorticoids, corticosteroids, etc. [ [94] , [95] , [96] ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the earliest research on rituximab in the treatment of pemphigus can be traced back to the successful treatment case published by Heizmann, M in 2001 [ 91 ], who proposed that rituximab may be an effective alternative drug for the treatment of PNP. Rituximab can be used alone to treat pemphigus [ 92 , 93 ] or in combination with glucocorticoids, corticosteroids, etc. [ [94] , [95] , [96] ].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all studies reported complete remission on treatment (n=20; 43.4%), off treatment (n=20; 43.4%), or complete remission without the status of ongoing treatment (n=3; 6.5%) or partial remission off treatment (n=2; 4.3%) at the final follow-up visit (n=45/46; 97.8%). Control of disease activity was reported in one case [ 33 ]. Relapses or flares were observed in 18 cases (39.1%) either minor or major, during initial follow-ups.…”
Section: Reviewmentioning
confidence: 99%
“…A total of 18 studies were shortlisted for qualitative synthesis [9,11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The characteristics of the included studies are comprehensively elaborated in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%